Constitutional Review and Dissenting Opinions in Nondemocracies: An Empirical Analysis of the Russian Constitutional Court, 1998–2018 - Khalikova, Yulia (Экономическая социология, 2020)
Whereas constitutional courts are associated with democracy and the rule of law, today, they these courts exist in nondemocracies, where they face direct threats to their existence or backlash from domestic actors. For a court to survive, it has to constantly strike a balance between performing the functions imposed by the ruler and trying not to lose its legitimacy. What is the role of constitutional courts in nondemocracies? When do they rule against the government, and when do they side with it? To what extent can regional governments, citizens, or political activists succeed in challenging the state? Given the higher risks judges in nondemocracies face, when do they author dissenting opinions? To answer these questions, I use a novel dataset on all final judgments issued by the Russian Constitutional Court (RCC) between 1998 and 2018 (N = 502). Using a regression analysis, I show how the outcomes of cases depend on who petitions the court and about what. First, the results show that the political regime and institutional settings matter—applications about the government’s structure have the lowest probabilities of being nullified but have higher probabilities of carrying a dissenting opinion. Additionally, judges dissent more when cases are brought by highlevel political actors, such as the president, federal parliament, and government. Second, social rights are an area of consensus among judges—the court is more likely to strike down laws that violate social rights, including social welfare and cases on antidiscrimination, and judges are less likely to dissent in such cases. When higher courts in nondemocracies exist—and as long as they benefit the ruler or ruling party—they tend to (1) avoid confrontation with the ruler and (2) shift their focus toward “safer” areas, which, in the Russian case, became advancing and protecting social rights.